Mechanisms of the high-temperature internal stresses relaxation during creep in alkali-halide single crystals - Matsokin, V.P.; Pakhomova, I.N. (Functional Materials, 2006)
The process of internal stresses relaxation at jump-like change of external stresses is experimentally investigated during creep of NaCI and KCI single crystals. The basic relaxation processes have been considered and some of those have been simulated.